Drawing as a Paralinguistic Phenomenon in Literary Texts (a Case Study of Tove Jansson’s Works) - Svetlana P. Cherkashina (Финно-угорский мир, 2025)
Introduction. The uniqueness of Tove Jansson’s persona lies in her dual role as both a writer and an artist who personally illustrated her own literary works, particularly the Moomin stories examined in this study. While Russian scholarship has so far focused solely on textual analysis of Jansson’s narratives, no dedicated studies have explored her illustrations. The aim of this study is to examine the correlation between the verbal component (expressed through occasionalisms) and iconic signs (represented by illustrations). The scholarly novelty of this work consists in investigating illustrations as elements of iconic code within the Moomin narratives. The article presents a methodological framework for analyzing drawings as iconic signs.